Model Pembelajaran dalam Penguatan Nilai Moderasi di Madrasah Diniyah: Penelitian - Kiky Nuruz Zakiyah; Muhammad Arif Syihabuddin (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Moderation in Islam is a religion that is Rahmatan lil 'alamin, not like the ideology of extremists who tend to prioritize a hard stance without compromise, or the ideology of liberal groups who often interpret religious teachings very loosely, freely, and even almost out of line with religious truth. This article aims to implement and develop the PAI learning model so that students behave moderately in Islam, both in faith, worship, and muamalah. So that it will produce a complete understanding of true religious moderation. The result of this article is to formulate an effective PAI learning model to be applied to students to optimize the values ​​of moderation so that they do not behave extreme in religion, both in terms of faith, worship, and socializing with others as exemplified by our prophet Muhammad sallallaahu 'alaihi wasallam.